Physical oceanography on the Namibian Shelf obtained by CTD measurements during RV Meteor cruise M157 (2019) - Volker Mohrholz; Sebastian Beier; Jens Faber; Toralf Heene; Martin Kolbe (PANGAEA, 2024)
The focus of hydrographic investigations during the cruise was on the impact of short term upwelling variability on oxygen and nutrient supply to the shelf, and on the response of primary production to short term upwelling peaks. Standard hydrographic parameters were gathered with a Seabird CTD along three transects at 17.3°S, 23°S and 25°S. We used a CTD SBE 911plus with a rosette water sampler to measure temperature, pressure, practical salinity, oxygen concentration, turbidity, fluorescence and irradiance. For details to all processing steps see Data Processing Report.